Targeting lysyl oxidase (LOX) overcomes chemotherapy resistance in triple negative breast cancer - Ozge Saatci (Nature Portfolio, 2020)
The development of chemoresistance is a major hurdle in triple negative breast cancer (TNBC). Here, the authors show that lysyl oxidase (LOX) is overexpressed in chemoresistant TNBCs, and when inhibited reduces collagen cross-linking, fibronectin fibril assembly, and downstream integrin signalling, overcoming resistance.